2020
DOI: 10.1111/acps.13142
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication exposure, clozapine, and pneumonia: results from a self‐controlled study

Abstract: medication exposure, clozapine, and pneumonia: results from a self-controlled study. Objective: By using a self-controlled design, we investigated whether antipsychotic medication exposure was associated with increased pneumonia risk and whether patients receiving clozapine were more likely to develop pneumonia than patients receiving other antipsychotic medications. Methods: Through nationwide health registers, we identified all outpatients with schizophrenia initiating antipsychotic treatment. First, we esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
1
17
0
2
Order By: Relevance
“…Despite the fact that clozapine is not indicated for dementia, its package insert was modified, too. The association between clozapine and pneumonia is supported by data from the Taiwan registry [37], other studies previously reviewed [49], and further verified by a mirror-image study in the Danish registry [157].…”
Section: Pneumoniasupporting
confidence: 56%
See 1 more Smart Citation
“…Despite the fact that clozapine is not indicated for dementia, its package insert was modified, too. The association between clozapine and pneumonia is supported by data from the Taiwan registry [37], other studies previously reviewed [49], and further verified by a mirror-image study in the Danish registry [157].…”
Section: Pneumoniasupporting
confidence: 56%
“…The lethality of pneumonia in clozapine patients is explained in that clozapine can contribute to pneumonia, and once pneumonia develops it can cause a clozapine intoxication; therefore, the combination of pneumonia and clozapine intoxication is highly lethal. This complex bidirectional association [162] is described in detail in online supplementary Box S7 [157,[163][164][165][166][167][168][169]. Our recommendations for decreasing the risk and lethality of pneumonia in clozapine patients are described in online supplementary Box S8 [65,162,170,171].…”
Section: Pneumoniamentioning
confidence: 99%
“…Therefore, the contributing effects of the severity level of mental illness on pneumonia needs to be further explored by future studies in clozapine patients. On the other hand, clozapine has specific effects independent of the greater severity of illness in the clozapine patients, since using mirror-image design in the Danish registry,Rhode et al 29 Rhode et al 29 found that clozapine gave the largest absolute increase in pneumonia risk although it did not reach significance, probably due to the relatively small sample size. In the year before clozapine, there were 1.22% (23/1872) patients with pneumonia and in the first year 1.87% (35/1872).…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 99%
“…This includes 79 pneumonia cases in 8355 patients who were naïve and started a first-generation antipsychotic, and 45 pneumonia cases in 8001 patients who were naïve and started a second-generation antipsychotic (5). article (5) described the following pneumonia rates over approximately 1 year: (i) 0.946% in 8355 antipsychotic-na€ ıve patients versus 0.682% after the first year of schizophrenia when treated with first-generation antipsychotics and (ii) 0.562% in another 8001 antipsychotic-na€ ıve patients versus 0.550% after the first year of schizophrenia when treated with second-generation antipsychotics.…”
mentioning
confidence: 99%